Biplanar ultrasound investigation of in vivo Achilles tendon displacement non‐uniformity. Issue 2 (19th December 2018) - Stenroth, Lauri; Thelen, Darryl; Franz, Jason
Abstract : The Achilles tendon is a common tendon for the medial and lateral gastrocnemius and soleus muscles. Non‐uniform Achilles tendon regional displacements have been observed in vivo which may result from non‐uniform muscle loading and intratendinous shearing. However, prior observations are limited to the sagittal plane. This study investigated Achilles tendon tissue displacement patterns during isometric plantarflexor contractions in the coronal and sagittal planes. Fourteen subjects (5 female, 9 male, 26 ± 3 year) performed maximal isometric plantarflexor contractions with the knee in full extension and flexed to 110°. An ultrasound transducer positioned over the free Achilles tendon collected beam formed radio frequency (RF) data at 70 frames/s. Localized tissue displacements were analyzed using a speckle tracking algorithm. We observed non‐uniform Achilles tendon tissue displacements in both imaging planes. Knee joint posture had no significant effect on tissue displacement patterns in either imaging plane. The non‐uniform Achilles tendon tissue displacements during loading may arise from the anatomical organization of the sub‐tendons associated with the three heads of the triceps surae. The biplanar investigation suggests that greatest displacements are localized to tissue likely to belong to soleus subtendon. This study adds novel information with possible implications for muscle coordination, function, and muscle‐tendon injury mechanisms.